Effect of derivatives in Finnish public companies - Salminen, Oskari (My University, 2025)
The purpose of this thesis is to investigate how derivatives affect the companies’ performance and market value. This thesis particularly focuses on currency, interest and commodity forwards, futures and options. The study is directed at OMXH25 companies. The use of derivatives has grown rapidly, and for that reason, it is important to study the effects. Different types of derivatives serve different purposes and therefore cannot be examined as a single, uniform category. Research has shown that, in general, currency derivatives have benefited companies, whereas similar results have not been observed for interest rate or commodity derivatives. However, these outcomes may vary significantly from one company to another. This study nevertheless demonstrates that derivatives do have an impact on corporate performance and market value. However, it cannot be conclusively stated that this impact is positive across all OMXH25 companies.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|